Exploring the relationship between hostel service quality and guests’ satisfaction: a comparison between younger and older guests - Lima, R.; Vicente, P. (e-Review of Tourism Research, 2017)
The hostel began as a type of accommodation chosen mainly by young travelers who appreciate staying in a place that allows them to meet other people and share information and experiences at a low price. Nowadays hostel clients are diverse and may include families, business tourists, and less young travelers. Despite the heterogeneity in the profile of hostel guests, research on the impact of service quality on hostel guests’ satisfaction has not considered that diversity. The purpose of this paper is to compare hostel preferences of young and older guests. We take data from a survey conducted with 223 hostel guests in Lisbon. The outcomes reveal that the main drivers of older guests' overall satisfaction are cleanliness and price whereas for younger guests it is primarily the staff’s competence and friendliness.